Fałszywa alternatywa, czyli meandry edukacji niesegregacyjnej - Fetzki, Tomasz (Studia Edukacyjne, 2018)
The paper is a voice in the discussion on mutual relations between special and non-segregative education. The aim of the author, professionally connected with special needs education, is to include in this discussion certain aspects and contexts till now present in a negligible extent and to show a perspective that is rarely encountered by researchers analyzing the issue, which can enrich and supplement the research process with significant elements.